Bacteriological study for Staphylococcus aureus bacteria selected from group of bacteria associated with diabetes wound patients in Al-Diwaniya city - Asst. Prof. Dr. Hussein , A. N.; Jabbar, A. A (Al-Qadisiyah Journal of Pure Science, 2017)
The samples of study were collected from Al-Diwaniya Teaching Hospital and taken from patients lobbies general surgery and micro-operations for a period of (1/12/2011) until (1/4/2012) and by 200 sample included 100 injuries sample of people with diabetes and another sample of 100 persons with non-diabetes.The bacterial isolates taken from skin injuries to different parts of the wounds and different ages for both sexes. The bacterial isolates mostly diagnosed using biochemical tests. While Vitek system was used in the diagnosis of some bacterial species, also chrom agar media used on establishing the diagnosis of some bacterial species, especially Staphylococcus aureus.Staph. aureus made first place (23% and 27%) as causing for wound infection in both categories of people with diabetes and patients followed Escherichia coli in second place (17% and 24%) and Pseudomonas aeruginosa in third place (10% and 7%) respectively. Also recorded in the current study cases of mixed injuries: bilateral, trilateral and quartet for wounds diabetics types bacterial different, while restricted to the injuries of single and binary only for wounds non-diabetics as well as the high percentage of isolates (23%) is the an container for any type bacterial wounds patients without diabetes compared isolated one only (1%) to diabetic wounds.The sensitivity of all isolates Staph. aureus causing infection wounds of patients with diabetes and the 42 isolation for all types of injuries single and mixed received in the current study were tested to 18 antibiotics by based on a method diffusion disks; all isolates given full resistant (100%) of antibiotics Amoxicillin, Ampicillin, PenicillinG and Amoxicillin-Clavulanic acid and semi complete (95.23%) to Carbencillin, While given a medium resistance (66.66%, 57.50%, 54.76%, 52.38% and 52.38%)ÙŠto antibiotics Methicillin, Erythromycin, Azithromycin, CephalothinÙŠandÙŠCefotaxime respectively. While equal resistance and sensitivity of the isolates to Oxacillin and Clindamycin by 50% for both, the showed weak resistance and high sensitivity to antibiotics Ceftriaxone, Trimethoprim, Gentamicin, Vancomycin, TetracyclineÙŠandÙŠChloramphenicol (45.23%, 40.47%, 28.57%, 21.42%, 16.66% and 7.14%) respectively. Which indicates that the percent of resistant isolates to antibiotics was higher than the sensitivity and on this basis was the mind of the isolates with multiple resistances to antibiotics.The viability of isolation 27 out of 42 belonging to the Staph. aureus was investigating as the most resistant to antibiotics on the production of ÃŸâ€“lactamase depending on fast standard iodine method, as showed 20(74.08%) isolate of its ability to produce enzymes versus 7(25.92%) isolates so unproductive.